#TITLE_ALTERNATIVE# - LAUREN SASTRA IRAWAN ( NIM : 15010055 ), SILVIA
H Building City Hall of DKI Jakarta is one of the office buildings that use bored pile foundations and diaphragm wall retaining structure. Given the importance of bottom structure functions as a support of upper structure, design and calculation of foundations and retaining structure must be done correctly. This final task performed a bearing capacity analysis of bored pile foundations and diaphragm wall of H Building City Hall of DKI Jakarta, including axial and lateral bearing capacity of a single pile and group pile, and also bearing capacity of D-Wall for an excavation. The analysis was done by manual calculation and software. APILE PLUS, LPILE PLUS, and GROUP are used in the analysis of bored pile foundations bearing capacity, PCA COL is used in design of reinforcement bar, and PLAXIS is used in the analysis of D-Wall bearing capacity. The result of bored pile foundations bearing capacity analysis show the need of foundations with diameter of 1,5 meters, with six pile types for BH 3 location and five pile types for BH 4 location. Bored pile foundations bearing capacity is measured by working load, settlement, and deflection happened to a single pile and group pile. Referring to analysis result, bored pile foundations bearing capacity met the safety criteria. Analysis result of D-Wall bearing capacity for an excavation show the need of retaining structure with strut IWF 400.400.13.21 as the bracing support within every elevation of excavation with influence area 4 meters long. D-Wall has 1 meter thickness and 37 meters tall, used along the excavation with 83,3 meters long, 50,3 meters wide, and 13,5 meters deep. The safety factor from PLAXIS is 3,7833.